Fatal pneumonia following maternal HSV-1 viraemia in late pregnancy. (30th September 2014) - Berardi, Alberto; Gallo, Claudio; Lugli, Licia; Guidotti, Isotta; Gargano, Giancarlo; Maccio, Livia; Pietrosemoli, Paola; Ferrari, Fabrizio
Abstract: Neonatal Herpes simplex virus (HSV) pneumonia without apparent accompanying disseminated infection is a rare condition. We describe a case of neonatal pneumonia following maternal HSV type 1 viraemia in late pregnancy. A review of the literature shows that cases of HSV presenting as pneumonia in the first week of life are the most severe form of neonatal HSV.